Prospek Indeks Tendensi Bisnis Jawa Timur Tahun 2009 - Soegiri, Hari (Jurnal Riset Ekonomi dan Bisnis, 2009)
Global economic conditions are depressed and full of uncertainty caused forecasting economic conditions, particularly in the short term becomes much more difficult. The economic growth rate projections made by various international agencies and investment banks are not much different from the government, with an estimated, namely in the range between 4.5% -5.5% during the year 2009. with the existence of such conditions is necessary to study about the prospects of a business tendency index that aims to analyze the plans and policies to be taken by the provincial administration against Tendecy Index Business (ITB) in East Java and the surrounding study was conducted in all districts / cities in the East Java Provincial Government. Data used in this research is secondary data and primary data.Keywords: Tendency, Business, Planning, Policy